Spread of Measles Virus D4-Hamburg, Europe, 2008–2011 - Annette Mankertz; Zefira Mihneva; Hermann Gold; Sigrid Baumgarte; Armin Baillot; Rudolph Helble; Hedwig Roggendorf; Golubinka Bosevska; Jasminka Nedeljkovic; Agata Makowka; Veronik Hutse; Heidemarie Holzmann; et al. (Emerging Infectious Diseases, 2011)
A new strain of measles virus, D4-Hamburg, was imported from London to Hamburg in December 2008 and subsequently spread to Bulgaria, where an outbreak of >24,300 cases was observed. We analyzed spread of the virus to demonstrate the importance of addressing hard-to-reach communities within the World Health Organization European Region regarding access to medical care and vaccination campaigns. The D4-Hamburg strain appeared during 2009–2011 in Poland, Ireland, Northern Ireland, Austria, Greece, Romania, Turkey, Macedonia, Serbia, Switzerland, and Belgium and was repeatedly reimported to Germany. The strain was present in Europe for >27 months and led to >25,000 cases in 12 countries. Spread of the virus was prevalently but not exclusively associated with travel by persons in the Roma ethnic group; because this travel extends beyond the borders of any European country, measures to prevent the spread of measles should be implemented by the region as a whole.